MANDATORY SPENDING DAN BELANJA INFRASTRUKTUR PADA PEMERINTAH KOTA PEKANBARU - Riyani, Desi; Yusrizal, Yusrizal (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The mandatory spending policy on infrastructure spending is actually intended to provide wider fiscal space to regions to further accelerate infrastructure development in order to encourage accelerated regional economic growth. This policy should have been implemented by the Pekanbaru City Government, but judging from the proportion of infrastructure spending over the last five years (2018-2022), it is still very small and has not met the minimum limit that has been determined. For this reason, it is necessary to carry out an analysis regarding the effectiveness of the mandatory spending policy for infrastructure spending in the Pekanbaru City Government. The analysis was carried out using descriptive qualitative methods and secondary data contained in the Regional Regulations regarding the Pekanbaru City APBD for 2018-2022. The results of the analysis show that mandatory spending actually becomes a burden on the Pekanbaru City APBD and narrows the regional government's fiscal space to formulate more effective and efficient budget allocation policies according to regional needs and potential. Mandatory spending is ineffective for the Pekanbaru City Government because it is not fully in line with performance-based budgeting principles and money follow program principles. As a recommendation, the Government needs to evaluate or review the mandatory spending policy and the Pekanbaru City Government must more consistently implement a performance-based budget system and commit to upholding the money follow program principle. Kebijakan mandatory spending belanja infrastruktur sesungguhnya dimaksudkan untuk memberikan ruang fiskal yang lebih luas kepada daerah untuk lebih memacu percepatan pembangunan infrastruktur guna mendorong percepatan pertumbuhan ekonomi daerah. Kebijakan tersebut semestinya sudah dijalankan oleh Pemerintah Kota Pekanbaru, namun dilihat dari proporsi belanja infrastruktur selama lima tahun terakhir (2018-2022) masih sangat kecil dan belum memenuhi batas minimal yang sudah ditentukan. Untuk itu perlu dilakukan analisis terkait efektifitas kebijakan mandatory spending belanja infrastruktur pada Pemerintah Kota Pekanbaru. Analisis dilakukan dengan mengunakan metode kualitatif deskriptif dan data sekunder yang tercantum dalam Peraturan Daerah tentang APBD Kota Pekanbaru tahun 2018-2022. Hasil analisis menunjukkan bahwa mandatory spending justru menjadi beban bagi APBD Kota Pekanbaru dan mempersempit ruang fiskal pemerintah daerah untuk merumuskan kebijakan alokasi anggaran yang lebih efektif dan efisien sesuai kebutuhan dan potensi daerah. Mandatory spending menjadi tidak efektif bagi Pemerintah Kota Pekanbaru karena tidak sepenuhnya sejalan dengan prinsip anggaran berbasis kinerja dan prinsip money follow programe. Sebagai rekomendasi, Pemerintah perlu melakukan evaluasi atau pengkajian ulang terhadap kebijakan mandatory spending dan kepada Pemerintah Kota Pekanbaru harus lebih konsisten menerapkan sistem anggran berbasis kinerja dan berkomitmen untuk menegakkan prinsip money follow program.